“The Book Of eternal brass”: The Bible and the Laws in William Blake’s The [First] Book of Urizen and Emanuel Swedenborg’s The Last Judgment - Spalovszky, Csaba József (FOCUS: Papers in English Literary and Cultural Studies, 2020)
William Blake was an artist and thinker whose character was as controversial as it was misunderstandable, even in his own time, let alone after his death. His works reflect a philosophical and theological system that is very diff erent from what we are used to in connection with the eighteenth and nineteenth centuries, more precisely, from our usual assumptions about the periods of the Enlightenment and Romanticism. The universe he created out of contemporary and earlier philosophical systems, the influence of religious movements like the Moravians and theologians like Emanuel Swedenborg or thinkers like Johann Kaspar Lavater, together with his own personal faith and idiosyncratic interpretations, might seem to be chaotic: a form of disorder, at least for the fi rst encounter. However, this apparent disorder is not a chaos, but the result of a new way of seeing the world, which is grounded in a unique understanding of the relationship between language and thinking.